2021
DOI: 10.3390/ijms22042110
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Techniques in Alzheimer’s Disease: A Review of Applications in Early Diagnosis and Longitudinal Monitoring

Abstract: Background. Alzheimer’s disease (AD) is a progressive neurodegenerative disorder affecting many individuals worldwide with no effective treatment to date. AD is characterized by the formation of senile plaques and neurofibrillary tangles, followed by neurodegeneration, which leads to cognitive decline and eventually death. Introduction. In AD, pathological changes occur many years before disease onset. Since disease-modifying therapies may be the most beneficial in the early stages of AD, biomarkers for the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
112
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 232 publications
(191 reference statements)
0
112
0
Order By: Relevance
“…The pathological processes underpinning AD involve the accumulation of Aβ1-42 in the brain decades prior to the onset of clinical symptoms, followed by a decrease in cortical metabolism [32][33][34]. Diagnosis and prognosis of AD are currently dependent on costly imaging approaches and neurophysiological tests [6,35]. CSF biomarkers directly reflect the brain environment and have been investigated for use in disease diagnosis and prognosis [7,36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pathological processes underpinning AD involve the accumulation of Aβ1-42 in the brain decades prior to the onset of clinical symptoms, followed by a decrease in cortical metabolism [32][33][34]. Diagnosis and prognosis of AD are currently dependent on costly imaging approaches and neurophysiological tests [6,35]. CSF biomarkers directly reflect the brain environment and have been investigated for use in disease diagnosis and prognosis [7,36].…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of currently available MR imaging-based approaches are evident [6]. As such, the development of plasma-based biomarkers for early diagnosis and disease-monitoring provides a key solution for treatment and prevention of AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 However, these findings are not specific to AD and the change might be very subtle during the MCI stage. Several novel imaging techniques have emerged, 7 and the radiomics approach, which extracts a large number of imaging features and mines invisible but meaningful data, has been under vigorous investigation in numerous fields such as the diagnosis of tumors, psychiatric disorders, and neurodegenerative diseases. 8 Tang et al applied this radiomics approach to the diagnosis of AD, and found that their method of extracting the requisite features from the whole cerebral cortex (using FreeSurfer), subcortical nucleus (using SPM12), and white matter lesions successfully predicted the time to progression (TTP) from MCI to AD, based on a 5-year follow-up and validation study.…”
mentioning
confidence: 99%